An n-Doped GaAs/AIGaAs multi-layered HEIWIP based terahertz photodetector - Jit S.; Weerasekara A.B.; Jayasinghe R.C.; Matsik S.G.; Perera A.G.U. (My University, 2025)
A heterojunction interfacial workfunction internal photoemission (HEIWIP) based terahertz photodetector with 12 periods of 1.3xI018em-3 Si-doped 20 nm GaAs emitter and undoped 80 nm Alo.09GaO.9~s barrier has been presented in this paper. Experimental results show a threshold barrier of - 4 THz (i.e. long wavelength cutoff wavelength Ac -70 mm) in forward bias operation and - 9 THz (Ac -34 mm) in the reverse bias operation. This type ofdiscrepancy in the threshold frequency is attributed to the formation ofan interface dipole between positively charged donor atoms migrated into the barrier region and negatively charged interface states.